PERAN KECUKUPAN MODAL (CAR) MEMEDIASI PENGARUH RESIKO KREDIT TERHADAP PROFITABILITAS - I Dewa Nyoman Usadha (Universitas Mahendradatta Denpasar, 2021)
The purpose of this study was to analyze the effect of credit risk on profitability. The relationship of the effect of credit risk on profitability (ROA) in a number of studies that have been developed found the effect of credit risk on profitability with negative results and there is also a significant positive effect. This research gap in current research needs to be mediated by new viables, so that credit risk does not affect the decline in the level of profitability. The mediating variable is Capital Adequacy (CAR).The results of the analysis of the Effect of Credit Risk on Profitability with Capital Adequacy as a Mediation Variable show that CAR is able to mediate the direct effect of NPL on ROA. Where the direct effect of NPL on ROA was originally valued at -0.562, but after the presence of CAR as a mediating variable, the effect of this relationship increased to 0.163. The more bad credit in a financial institution, the more it will cause losses. To cover this loss, the financial institution returns it from the capital it owns so that it will reduce the CAR value of the cooperative